A Flotation Study for Effective Separation of the Heavy Mineral Sands - Owada S; Takiuchi T; Kurita M (The Australasian Institute of Mining and Metallurgy, 1993)
This paper describes the possibility of the application of flotation to the separation of monazite from xenotime and of columbite from ferberite, which have been said to be difficult with generally used physical beneficiation methods. For Malaysian monazite and xenotime samples, a great difference is observed between the flotation recoveries at pH 7.5 using 1.0 x 10-4mol/1 dodecylammonium chloride (DAC). The grade and recovery of columbite in the binary flotation with both minerals result in 85 per cent and 67 per cent in the cleaning froth and 91 per cent and 51 per cent in the re-cleaning froth, without adding any scavenging stages. For monazite samples from various localities, the flotability is dominated by the electrostatic interaction between mineral surface and collector ion using DAC as collector, but the singular decrease of flotation is observed in the sample of which the crystallinity is low and the surface structure is rugged and complex. Otherwise, ferric ion in the flotation system probably dissolved from mineral is found to activate the flotation using sodium dodecylsulfate as collector. For columbite and ferberite, the separation is judged possible at pH 3.0 using 1.0 x 10'3mo1/l sodium oleate (NaOl) from the single flotation results of each mineral. In the binary flotation, however, columbite recovery in the froth is greatly diminished below that expected. This would be because NaOl is prevented from adsorbing on the columbite surface of which the charge is transformed more negative side by the specific adsorption of the tungstate ion dissolved from ferberite.